New clinical insights into the treatment of benign uretero‐ileal anastomotic stricture following radical cystectomy and urinary diversion - Yixuan Mou; Cenchao Yao; Zhenghong Liu; Pu Zhang; Xiaolong Qi; Dahong Zhang; Yiyang Chen; Weiwen Yu; Shuai Wang (Cancer Medicine)
Abstract Background Benign uretero‐ileal anastomotic stricture (UIAS) is a potentially serious complication that can arise after radical cystectomy (RC) and subsequent urinary diversion. To preserve residual renal function and improve prognosis, it is crucial to derive insights from experience and tailor individualized treatment strategies for different patients. Patients and Methods From October 2014 to June 2021, a total of 47 patients with benign UIAS underwent endoscopic management (n = 19) or reimplantation surgery (n = 28). The basic data, perioperative conditions, and postoperative outcomes of the two groups were compared and analyzed to evaluate efficacy. Results Comparing preoperative and postoperative clinical efficacy within the same group, the endoscopic group showed no significant differences in creatinine and blood urea nitrogen (BUN) levels before surgery or after extubation (p > 0.05). However, significant differences were observed in glomerular filtration rate (GFR) levels on the affected side before surgery and after extubation (p < 0.05). In contrast, the laparoscopic reimplantation group did not exhibit significant differences in creatinine, BUN, or GFR levels of affected side before surgery and after extubation (p > 0.05). Postoperative clinical efficacy showed no significant difference in creatinine and BUN levels between the two groups (p > 0.05). However, GFR values of affected side in the endoscopic treatment group decreased more than those in the laparoscopic reimplantation group (p < 0.05). Additionally, the laparoscopic reimplantation group was able to remove the single‐J tube earlier than the endoscopic treatment group (p < 0.05), had a lower recurrence rate of hydronephrosis after extubation (p < 0.05), and experienced a later onset of hydronephrosis compared to the endoscopic treatment group (p < 0.05). Conclusions Based on our experience in treating UIAS following RC combined with urinary diversion, laparoscopic reimplantation effectively addresses the issue of UIAS, allowing for the removal of the ureteral stent relatively soon after surgery. This approach maintains long‐term ureteral patency, preserves residual renal function, reduces the risk of ureteral restenosis and hydronephrosis, and has demonstrated superior therapeutic outcomes in this study.